An explication of the dual nature of narcissism in Patrick White's novel The solid mandala - Watts, Jacqueline Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The focus of this thesis has been to engage in a hermeneutic dialogue with Patrick White's novel The solid mandala, to provide an explication of the dual nature of narcissistic wounding. To this end a brief review of Patrick White's novels is given, which traces a thematic development of the hero's strivings to attain wholeness and merger with an idealized image. This struggle is understood to reflect man's strivings to return to a state of omnipotent fusion with the maternal image, be it God, nature, the idealized other, or the self. Literature which reflects the dual nature of narcissistic wounding is reviewed, and the concept of narcissism is traced from the historical roots of Freud, to current understandings of the function and experience of narcissism. Emphasis is given to understanding the experiential nature of narcissistic wounding. As such it is implied that narcissism is a normal developmental component which requires the facilitation of containment and reflection for its transformation into appropriate adult functioning. The importance of the maternal environment is discussed, together with the various theoretical conceptualizations of the consequences of failure of the environment. The hermeneutic dialogue with the novel's description of the experiences of the twins, Waldo and Arthur provides the basis for an amplification of the experience of narcissistic wounding. This amplification is used as clinical material from which a number of psychoanalytic formulations are drawn. These formulations are supported by a number of clinical examples from the researcher's own practice. There appears to be evidence for the value of focusing on the dual nature of the experience of narcissistic wounding. This focus reveals two aspects of experience, a damaged, positive, libidinal aspect and a defensive, pathological destructive aspect. Amplification of these two aspects of experience contribute to further the understanding of the conflictual experience of narcissistic wounding, and suggest the necessity for such an understanding for effective therapeutic intervention
Keywords: White, Patrick, 1912-1990. The Solid Mandala; White, Patrick, 1912-1990 -- Criticism and interpretation